Development of human ectocervical tissue models with physiologic endocrine and paracrine signaling. Issue 3 (13th May 2020) - McKinnon, Kelly E; Sensharma, Rhitwika; Williams, Chloe; Ravix, Jovanka; Getsios, Spiro; Woodruff, Teresa K
Abstract: There is a shortage of research models that adequately represent the unique mucosal environment of human ectocervix, limiting development of new therapies for treating infertility, infection, or cancer. We developed three microphysiologic human ectocervix models to study hormone action during homeostasis. First, we reconstructed ectocervix using decellularized extracellular matrix scaffolds, which supported cell integration and could be clinically useful. Secondly, we generated organotypic systems consisting of ectocervical explants co-cultured with murine ovaries or cycling exogenous hormones, which mimicked human menstrual cycles. Finally, we engineered ectocervix tissue consisting of tissue-specific stromal-equivalents and fully-differentiated epithelium that mimicked in vivo physiology, including squamous maturation, hormone response, and mucin production, and remained viable for 28 days in vitro . The localization of differentiation-dependent mucins in native and engineered tissue was identified for the first time, which will allow increased efficiency in mucin targeting for drug delivery. In summary, we developed and characterized three microphysiologic human ectocervical tissue models that will be useful for a variety of research applications, including preventative and therapeutic treatments, drug and toxicology studies, and fundamental research on hormone action in a historically understudied tissue that is critical for women's health.